Dual extended composite right/left‐handed transmission line metamaterial. Issue 5 (21st January 2018) - Shahraki, Hamed; Afrooz, Kambiz; Hakimi, Ahmad
Abstract: The new concept of dual extended composite right/left‐handed transmission line (D‐ECRLH TL), with 2 right handed and 2 left handed frequency bands is presented. The D‐ECRLH TL and extended composite right/left handed transmission line are structurally dual. Therefore, the proposed TL shows the dual properties of the ECRLH TL. The D‐ECRLH indeed behaves as a dual‐band bandstop filter, in opposition to the ECRLH which is a dual‐band bandpass one. In contrast, the D‐ECRLH creates an unlimited LH bandwidth. In this article, the transmission parameters and the fundamental properties of the D‐ECRLH TL (dispersion and impedance diagrams) are investigated. The results show that the proposed structure is suitable to design the quad‐band microwave circuits and systems. A prototype of the proposed D‐ECRLH unit cell is realized by the microstrip technology. The good agreement between the measurement and simulation results confirms the realizability of the proposed structure.